2018
DOI: 10.1002/jts.22330
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Role of Difficulties Regulating Positive Emotions in Posttraumatic Stress Disorder

Abstract: Emotion regulation difficulties have been theoretically and empirically linked to posttraumatic stress disorder (PTSD). Previous research, however, has focused almost exclusively on difficulties regulating negative emotions. In this study, we explored the nature of difficulties regulating positive emotions in PTSD. Participants were women who had experienced domestic violence (N = 210; 48.6% African American; Mage = 36.14 years). Higher levels of nonacceptance of positive emotions, difficulties engaging in goa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 31 publications
(39 reference statements)
4
66
0
Order By: Relevance
“…Emotion dysregulation is a multi-faceted construct involving maladaptive ways of responding to emotions, including: (a) a lack of awareness, understanding, and acceptance of emotions; (b) the inability to control behaviors when experiencing emotional distress; (c) a lack of access to situationally appropriate strategies for modulating the duration and/or intensity of emotional responses in order to meet individual goals and situational demands; and (d) an unwillingness to experience emotional distress as part of pursuing meaningful activities in life (Gratz & Roemer, 2004;Gratz & Tull, 2010). Research suggests that higher levels of emotion dysregulation are associated with more severe PTSD symptoms among women victims of IPV (Lilly & Hong, 2013;Lilly, London, & Bridgett, 2014;Weiss, Darosh, Contractor, Forkus, Dixon-Gordon, & Sullivan, 2018;Weiss, Dixon-Gordon, Peasant, & Sullivan, 2018). For instance, among community women with a history of IPV, Lilly and Hong (2013) found that emotion dysregulation was significantly positively related to PTSD severity at zero-order and when accounting for other known risk factors such as avoidant attachment and maladaptive cognitions.…”
mentioning
confidence: 99%
“…Emotion dysregulation is a multi-faceted construct involving maladaptive ways of responding to emotions, including: (a) a lack of awareness, understanding, and acceptance of emotions; (b) the inability to control behaviors when experiencing emotional distress; (c) a lack of access to situationally appropriate strategies for modulating the duration and/or intensity of emotional responses in order to meet individual goals and situational demands; and (d) an unwillingness to experience emotional distress as part of pursuing meaningful activities in life (Gratz & Roemer, 2004;Gratz & Tull, 2010). Research suggests that higher levels of emotion dysregulation are associated with more severe PTSD symptoms among women victims of IPV (Lilly & Hong, 2013;Lilly, London, & Bridgett, 2014;Weiss, Darosh, Contractor, Forkus, Dixon-Gordon, & Sullivan, 2018;Weiss, Dixon-Gordon, Peasant, & Sullivan, 2018). For instance, among community women with a history of IPV, Lilly and Hong (2013) found that emotion dysregulation was significantly positively related to PTSD severity at zero-order and when accounting for other known risk factors such as avoidant attachment and maladaptive cognitions.…”
mentioning
confidence: 99%
“…Indeed, tracking emotional intensity/valence may be a validating indicator of the hypothesised affect change that should accompany retrieval of positive memories (Pennebaker, ). One clinician added that tracking emotional intensity/valence may prevent avoidance of (positive) emotions, which is relevant, given that trauma‐exposed individuals may think that they do not deserve positive thoughts/emotions (Norman, Wilkins, Myers, & Allard, ) and may experience dysregulation related to positive emotions (Weiss, Dixon‐Gordon, Peasant, & Sullivan, ; Weiss, Nelson, Contractor, & Sullivan, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, elevated responsiveness to environmental stimuli may cause PA to be perceived as aversive and, consequently, to be blocked (cf. Contractor et al, 2018 ; Weiss et al, 2018 , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although studies indicated that PTS is not associated with an inability to experience PA per se (Dornbach-Bender et al, 2020 ), there is gradually growing evidence that the dysregulation of PA does contribute to PTS. For instance, in a study among women exposed to domestic violence, Weiss, Dixon-Gordon, Peasant, and Sullivan ( 2018 ) found that higher levels of nonacceptance of positive emotions, difficulties engaging in goal-directed behaviours, and difficulties to control impulsive behaviours when experiencing positive emotions were related to more severe PTS. In a further study, PA dysregulation was found to predict PTS, when controlling NA dysregulation (Weiss, Nelson, Contractor, & Sullivan, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation